Making An Aquascape Using Ornaments From Plastic Waste For Proklim Cadres RW 02 Sungai Miai Village, North Banjarmasin : Pembuatan Akuaskap Menggunakan Ornamen Dari Sampah Plastik Untuk Kader Proklim RW 02 Kelurahan Sungai Miai Banjarmasin Utara - Noor Arida Fauzana; Pahmi Ansyari; Slamat; Agung Nugroho (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Aquascape is the art of designing underwater gardens. The main elements of aquascape is the presence of plants, stones, wood and ornamental fish as ornaments in containers such as aquariums. Usually, aquascape use ornaments from nature as an aesthetic ecosystem in the aquarium, but their existence requires a relatively expensive cost. The purpose is to provide education and training in making aquascape using ornaments from plastic waste either from drink bottles, refillable packaging or plastic bags to the community and Proklim (Program Kampung Iklim) RW02 cadres of Sungai Miai Village, North Banjarmasin. The activity methods was delivered by of counseling, demonstration, training and mentoring. The results showed that there was an increase in the knowledge of the partner group from a score of 1.49 to 18.1 or an increase of 1170% and an increase the skills from a score of 7 to 16.64 or an increase of 137.76%. The supporting factor is that the partner group already has the skills to process plastic waste into various decorations, so that it can be used as an aquascape ornaments. The inhibiting factor is that the PDAM water used for the aquascape must be precipitated.